Figure 3 from: Fernandez-Triana J (2014) New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. Biodiversity Data Journal 2: e1040. https://doi.org/10.3897/BDJ.2.e1040 - Fernandez-Triana, Jose (Zenodo, 2014)
Figure 3 - Microgaster deductor specimen from Abisko, Sweden. Habitus, dorsal view (left), details of fore wing (top right) and tarsal claws (bottom right). Red arrows show tarsal claw lobes, and vein r of fore wing.